Evaluation of the Metabolic Production from the Co-Culture of Saccharicola sp. and Botryosphaeria parva, an Endophytic Fungi Associated with Eugenia jambolana Lam. - Costa, Mayra F. [UNESP] (2023)
A new compound, (6R,7S,2E,4E)-6,7-dihydroxy-4,6-dimethylocta-2,4-dienoic acid (1), together with eight known compounds were isolated from the co-culture of Saccharicola sp. and Botryosphaeria parva, an endophytic fungi associated with Eugenia jambolana Lam. (Myrtaceae) plant species. The structures were elucidated by spectroscopic analysis of the one-dimensional (1D) and two-dimensional (2D) nuclear magnetic resonance (NMR) and mass spectrometry (MS) data as well as by comparison with literature data. The bioactivity (antioxidant and antifungal) of the crude EtOAc was evaluated. All crude extracts presented antioxidant activity and only the crude extract from the co-culture was active on the fungus Cladosporium sphaerospermum. This investigation contributed to the knowledge about the metabolic production of two endophytic fungi Saccharicola sp. and Botryosphaeria parva in co-culture, once, until the present date, there are no studies in the literature that report the understanding of the chemical interaction of both grown in the same environment.